Effects of nonsurgical, minimally or noninvasive therapies for urinary incontinence due to neurogenic bladder: a systematic review and meta-analysis - Mohammed Usman Ali; Kenneth Nai-Kuen Fong; Priya Kannan; Umar Muhammad Bello; Georg S. Kranz (SAGE Publishing, 2022)
Objective: To determine the effects of nonsurgical, minimally or noninvasive therapies on urge urinary incontinence (UUI) symptoms and quality of life (QoL) in individuals with neurogenic bladder (NGB). Data Sources: Cochrane library, EMBASE, MEDLINE, PEDro, Scopus, and Web of Science databases were searched from inception to September 2021. Review Methods: Randomized controlled trials that compared therapies such as intravaginal electrical stimulation (IVES), transcutaneous electrical nerve stimulation (TENS), neuromuscular electrical stimulation (NMES), transcutaneous tibial nerve stimulation (TTNS), pelvic floor muscle training (PFMT), and behavioural therapy (BT) to control were included. Study screening, data extraction, and study quality assessments were performed by two independent authors. Results: Fourteen trials with 804 participants were included in the study after screening of 4281 potentially relevant articles. Meta-analyses revealed a significant effect of electrical stimulation on UUI due to multiple sclerosis (standardized mean difference (SMD): −0.614; 95% confidence interval (CI): −1.023, −0.206; p = 0.003) and stroke (SMD: −2.639; 95% CI: −3.804, −1.474; p = 0.000). The pooled analyses of TTNS (weighted mean difference (WMD): −12.406; 95% CI: −16.015, −8.797; p = 0.000) and BT (WMD: −9.117; 95% CI: −14.746, −3.487; p = 0.002) revealed significant effects of these interventions on QoL in people with Parkinson's disease. However, meta-analyses revealed nonsignificant effects for PFMT (WMD: −0.751; 95% CI: −2.426, 0.924; p = 0.380) and BT (WMD: −0.597; 95% CI: −1.278, 0.083; p = 0.085) on UUI due to Parkinson's disease. Conclusions: Our meta-analyses found electrical stimulation to be beneficial for improving the symptoms of UUI among people with multiple sclerosis and those with stroke. Our review also revealed that TTNS and BT might improve QoL for people with NGB due to Parkinson's disease, although the effects of PFMT and BT on UUI warrant further investigation.